Factors Affecting The Effectiveness Of Ais “Sakti” Based On Delone And Mclean (2003) Modified Models - Ralind, Ardhitian Herdhiantha; Baridwan, Zaki; Prastiwi, Arum (E-Jurnal Akuntansi, 2024)
The aim of this research is to empirically test the impact of system quality, information quality, management support on the perceived usefulness, user satisfaction and the effectiveness of accounting information systems (AIS). The sample was used by 143 respondents from SAKTI users in the Sidoarjo Mud Control Center, the Brantas River Region Hall, and the East Java National Road Implementation Hall-Bali Ministry of PUPR. This research uses primary data obtained from the questionnaire. Data collection techniques using convenience sampling and data analysis techniques using SEM-PLS. Results of system quality analysis do not affect user satisfaction, information quality does not affect usefulness, system quality affects usefulness, quality of information affects user satisfactions, management support affects customer satisfaction and usefulness, usefulness affects user satisfactions and the effectiveness of AIS, user satisfactions affects the effectiveness of AIS. Implications of this research are the development of models to measure the effectiveness of AIS and also as a reference for improvements in SAKTI applications later on. Keywords: Effectiveness of AIS, SAKTI, ISSM Delone and Mclean, Management Support, Mandatory